Model for analysing the social and economic impact of child undernutrition in Latin America - Martínez, Rodrigo (CEPAL SantiagoCL, 2007)
Presents a proposal for a theoretical framework encompassing the principal factors causing undernutrition, their corresponding specific variables and interrelationships, and the consequences arising out of this scourge. Provides also, a methodology for analyzing them and estimating the associated costs, based primarily on data currently available in the countries of the region.